New ADA/EASD Guidelines Focus on Patient-Centered Care - Buckley, Rita (MD Conference Express, 2012)
The International Diabetes Federation estimates that up to 1 adult in 10 will have diabetes by 2030 [International Diabetes Federation. IDF Diabetes Atlas. 5th ed. 2009]. To better handle this impending crisis, the latest American Diabetes Association and European Association for the Study of Diabetes guidelines present a new perspective on the management of hyperglycemia in type 2 diabetes (T2DM) [Inzucchi SE et al. Diabetes Care 2012; Inzucchi SE et al. Diabetologia 2012].